Transformation of the Fungal Soybean Pathogen Cercospora kikuchii with the Selectable Marker bar - Upchurch, Robert G. (1994)
An improved transformation protocol, utilizing selection for resistance to the herbicide bialaphos, has been developed for the plant pathogenic fungus Cercospora kikuchii. Stable, bialaphos-resistant transformants are recovered at frequencies eight times higher than those achieved with the previous system that was based on selection for benomyl resistance. In addition to C. kikuchii, this improved method can also be used to transform other species of Cercospora.